Evaluasi Kebijakan Tarif Cukai Rokok Elektrik Guna Mendorong Persaingan Usaha Yang Sehat - Mukti Fajar ND (Jurnal Penegakan Hukum Indonesia, 2022)
The tariff on the open and closed liquid system of e-cigarettes has a significant gap. Both products have the same characteristics, with the main difference in the liquid-filling mechanism. The open system allows the user to fill in manually, while in the closed system the liquid and shells are just installed into the device. Even though they both contain the same substance, the tariff on the closed system (Rp. 6,030/ml) is 14 times higher than the open system (Rp. 445/ml). Therefore this study is focussing on aspects of tariff policy on e-cigarettes from the competition law. This research is directed to evaluate the e-cigarette tariff policy in competition law as an effort to strengthen the function and role of the government to promote fairness in competition. This research was conducted using a normative/doctrinal juridical method. The results of the study indicate that differences in tariff rates have caused polemics not only from a business standpoint but also from the role and function of the government as a regulator of fair business competition. Separation and differentiation of tariff rates on Open Systems and Closed Systems have led to unequal treatment in business competition. This policy is detrimental to the business actors because they have to pay a tariff rate 14 times higher than that of their competitors. Whereas in order to carry out its functions and roles, the government should act as the competition policy maker and as an advocate of competition. Thus the government as a regulator plays an important role to create responsive and fair policies for business competition.